Media-Based Agility Training Model of Badminton Games for Students of Universitas Negeri Jakarta Badminton Club - Khaeroni, Khaeroni; Hariyanto, Krisnawan (Gladi : Jurnal Ilmu Keolahragaan, 2022)
Badminton athletes need agility to place the shuttlecock into an empty opponent’s field so that the opponent finds it difficult to return the ball. So, the purpose of this study is to create an exercise model to improve agility in the badminton game. Making this model through five stages, namely analysis, design, development, implementation and evaluation with the type of development research and development from Robert Maribe Branch. The results of the developed model were validated by three experts in badminton. Based on the five stages of research (analysis, design, development, implementation and evaluation), the results obtained that the training model developed was feasible and could be applied to badminton club athletes at the State University of Jakarta. The conclusion of the research is the media-based agility training model of the badminton game can be applied to the training process that aims to improve the athlete’s agility.